2014
DOI: 10.1177/1933719114536473
|View full text |Cite
|
Sign up to set email alerts
|

Peptides in Seminal Fluid and Their Role in Infertility: A Potential Role for Opiorphin Inhibition of Neutral Endopeptidase Activity as a Clinically Relevant Modulator of Sperm Motility: A Review

Abstract: Infertility is a devastating medical condition that adversely affects emotional health and well-being of couples who desire pregnancy and parenthood. The overall demographic data suggest that the indication for more than one-third of assisted reproductive technology cycles performed in the United States includes male factor infertility. There is increasing recognition of the role that peptides present in seminal plasma have in determining sperm motility. Several recent studies suggest that peptidases, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Apart from synthetic NEP inhibitors there are some natural endogenous NEP inhibitors, including the stress-response peptide, sialorphin ( Rougeot et al, 2003 ) and “opiorphins”, which possess strong analgesic properties ( Wisner et al, 2006 ). Some studies have also suggested that opiorphins promote sperm motility which adds another important role to the list of NEP functions and therapeutic avenues ( Bosler et al, 2014 ). Role of NEP in development and modulation of pain, stress response, addiction, sexuality, and food intake has recently been reviewed in ( Roques, 2018 ).…”
Section: Nep As a Therapeutic Targetmentioning
confidence: 99%
“…Apart from synthetic NEP inhibitors there are some natural endogenous NEP inhibitors, including the stress-response peptide, sialorphin ( Rougeot et al, 2003 ) and “opiorphins”, which possess strong analgesic properties ( Wisner et al, 2006 ). Some studies have also suggested that opiorphins promote sperm motility which adds another important role to the list of NEP functions and therapeutic avenues ( Bosler et al, 2014 ). Role of NEP in development and modulation of pain, stress response, addiction, sexuality, and food intake has recently been reviewed in ( Roques, 2018 ).…”
Section: Nep As a Therapeutic Targetmentioning
confidence: 99%
“…Although it has been postulated that small amounts of prostatic fluid protect spermatozoa from capacitation and oxidative stress (Nöthling et al, , ), detailed effects on fertility are not well understood. Different to this, correlations between male fertility and the composition of seminal plasma are well established in human medicine (Bosler, Davies, & Neal‐Perry, ; Fallah, Mohammad‐Hasani, & Colagar, ). In contrast, information from the dog is sparse and data presented in the literature are based on small numbers of ejaculates/dogs only.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the seminal plasma proteins play a potential role in the regulation of male fertility [ 29 ]. However, the relationship between APN and sperm/male fertility reported by several investigators remains discordant [ 13 , 15 , 17 , 18 ]. In the present study, we supplemented APN in sperm culture medium during capacitation in order to understand the specific role of APN in the regulation of sperm function(s) and fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of Arienti et al ., localization of this enzyme has also been confirmed in human sperm membrane by another research group [ 15 ]. Although a number of observations made in the laboratory and during human clinical studies have suggested a possible role for altered APN levels in several diseases [ 16 , 17 ], the underlying role of this enzyme in regulating male fertility remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%